Fast and reliable detection of SARS-CoV-2 antibodies based on surface plasmon resonance - Basso, Caroline Rodrigues [UNESP]; Malossi, Camila Dantas [UNESP]; Haisi, Amanda [UNESP]; De Albuquerque Pedrosa, Valber [UNESP]; Barbosa, Alexandre Naime [UNESP]; Grotto, Rejane Tommasini [UNESP]; Araujo Junior, João Pessoa [UNESP] (Royal Society of Chemistry (RSC), 2021)
Researchers worldwide have been studying alternatives to detect SARS-CoV-2 (COVID-19), and accurate and timely diagnosis is crucial for controlling the outbreaks of the disease. Surface plasmon resonance (SPR) is an effective strategy based on antibodies, and it can be used for simple and fast detection of antibodies due to COVID-19 infection. Accordingly, this paper reports on the highly sensitive and specific detection of antibody responses to SARS-CoV-2 spike (S) and nucleocapsid (N) proteins in COVID-19 patients. In this methodology, spike (S) and nucleocapsid (N) proteins belonging to the coronavirus genome were immobilized on the surface of a gold sensor using self-assembled monolayers. Previously, serum from COVID-19 patients was screened by immunochromatography-based COVID-19 IgG rapid test and/or ELISA in house to determine the presence of IgG titers. Serum from COVID-19-positive patients presenting with IgG were added on the surface and, at the time they bound to proteins, they caused refractive changes in the SPR angle. The antibody detection limit was determined through successive injections into the SPR apparatus-these injections ranged from pure (without dilution) to 1 : 200 μL. The system has shown good reproducibility between runs after coated surface regeneration with 0.1 M glycine-HCl solution (pH 3.0); all experiments were tested in triplicate. The antibodies targeted both S and N fragments and gave a high assay sensitivity by identifying 19 out of 20 COVID-19-positive patients. Most importantly, the assay time took less than 10 min. The results of this study indicate that the proposed simple strategy demonstrates high sensitivity and time-saving in the detection of SARS-CoV-2 response antibodies.